A training program to improve neuromuscular and performance indices in female high school soccer players - Noyes, F. R.; Barber-Westin, S. D.; Tutalo Smith, S. T.; Campbell, T. (The Journal of Strength and Conditioning Research, 2013)
The purpose of this study was to determine if a sports-specific anterior cruciate ligament injury prevention training program could improve neuromuscular and performance indices in female high school soccer players. We combined components from a published knee ligament intervention program for jump and strength training with other exercises and drills to improve speed, agility, overall strength, and aerobic fitness. We hypothesized that this program would significantly improve neuromuscular and athletic performance indices in high school female soccer players. The supervised 6-week program was done 3 d/wk for 90-120 minutes per session on the soccer fields and weight room facilities in area high schools. In phase 1, 62 athletes underwent a video drop-jump test, t-test, 2 vertical jump tests, and a 37-m sprint test before and upon completion of the training program. In phase 2, 62 other athletes underwent a multistage fitness test before and after training. There were significant improvements in the mean absolute knee separation distance (p < 0.0001), mean absolute ankle separation distance (p < 0.0001), and mean normalized knee separation distance (p < 0.0001) on the drop-jump, indicating a more neutral lower limb alignment on landing. Significant improvements were found in the t-test (p < 0.0001), estimated maximal aerobic power (p < 0.0001), 37-m sprint test (p = 0.02), and in the 2-step approach vertical jump test (p = 0.04). This is the first study we are aware of that demonstrated the effectiveness of a knee ligament injury prevention training program in improving athletic performance indices in high school female soccer players. Future studies will determine if these findings improve athlete compliance and team participation in knee ligament injury intervention training.